2017
DOI: 10.1177/1359105317705984
|View full text |Cite
|
Sign up to set email alerts
|

The importance of relationships in treatment for chronic leg ulceration

Abstract: Leg ulcers are a hard-to-heal wound that can have a profound impact on the lives of those that they affect. While a significant body of evidence has explored the efficacy of various treatments for leg ulcers, little research has addressed the patient experience of such treatment. A total of 21 participants were recruited for this qualitative interview study, exploring patient's experiences of non-surgical treatment for leg ulcers. Thematic analysis identified two major themes, 'Failure' and 'Powerlessness', as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…If communication fails, the staff risks losing sight of the patient, meaning that the lack of progress and healing will be in focus. The perception that communication between staff members also fails has been described before 41 . Tollow and Ogden found that the treatment approach can differ between staff members, leading to decreased confidence on the part of the patient, another confirmation of this study's result.…”
Section: Discussionsupporting
confidence: 83%
“…If communication fails, the staff risks losing sight of the patient, meaning that the lack of progress and healing will be in focus. The perception that communication between staff members also fails has been described before 41 . Tollow and Ogden found that the treatment approach can differ between staff members, leading to decreased confidence on the part of the patient, another confirmation of this study's result.…”
Section: Discussionsupporting
confidence: 83%
“…32 To help patients deal with chronic wounds without being knocked down by powerlessness, wound nurses or therapists should pay attention to signs of powerlessness. 15,33 Persistent feeling of powerlessness massively affects not only psychological but also physical health, it should be assessed with early intervention for better health outcome. 34 Also, wound nurses need a valid and reliable instrument so as to better understand patients' powerlessness experience in wound healing clinic.…”
Section: Discussionmentioning
confidence: 99%
“…When individuals are faced with difficulties, they often perceive lack of power . To help patients deal with chronic wounds without being knocked down by powerlessness, wound nurses or therapists should pay attention to signs of powerlessness . Persistent feeling of powerlessness massively affects not only psychological but also physical health, it should be assessed with early intervention for better health outcome .…”
Section: Discussionmentioning
confidence: 99%
“…Leg ulcers are hard‐to‐heal wounds localised on the lower leg or foot commonly caused by venous insufficiency, arterial insufficiency, diabetes and rheumatoid arthritis (Tollow & Ogden, 2019). The chronicity of wounds is defined as a failure ‘to proceed through an orderly and timely process to produce anatomic and functional integrity’ (Lazarus et al, 1994).…”
Section: Introductionmentioning
confidence: 99%